A PHENOMENA OF WORK FROM HOME POLICY IN DEALING WITH THE COVID-19 PANDEMIC: FENOMENA KEBIJAKAN BEKERJA DARI RUMAH (WORK FROM HOME) DALAM MENGADAPI PANDEMI COVID-19 - Mujahid Shiroth Rasyid Jauhari; Hanif Achmad Rasyid Jauhari (Journal of Public Administration, 2022)
This scientific paper discusses the phenomenon of public policy, namely the policy of working from home (Work From Home) due to the co-19 pandemic. The author's purpose in choosing this title is because the Covid-19 pandemic is not only about health problems or prolonged transmission of the virus which results in death, but also about service, physiological, communication, psychological problems, and the tendency to overuse gadgets. This policy that has been regulated by the government by working from home (Work From Home) is in order to reduce cases of contracting the Covid-19 virus and can reduce the death rate which continues to grow, other policies regulated by the government also require every citizen to take vaccinations. Of course the work from home policy has advantages and disadvantages in several aspects of life and work. This scientific work seeks to provide an analysis of the Work From Home phenomenon during the Covid-19 pandemic. The Covid-19 pandemic has brought major changes to all levels of society in various aspects, including the socio-cultural aspects. The Covid-19 pandemic forced restrictions on social activities between individuals, giving rise to habits that were different from their previous lives. In other words, this pandemic has given rise to a new societal culture to respond to existing policies of limiting social activities. The results of the author's analysis, the Covid-19 pandemic is still happening today.